Reklamy lokali gastronomicznych w „Dzienniku Bydgoskim” jako świadectwo lokalnej kultury kulinarnej (Kronika Bydgoska, 2018)
Gastronomy and its changes in a period between the late 19th and early 20th century is a topic that has not yet been adequately studied, and not too many works have been dedicated to Bydgoszcz and its culinary traditions. These days, we notice in our culture the trend toward a return to traditional cuisine and preservation of old culinary traditions, for instance through the use of old recipes. Such return to the roots is not only fashionable, but also serves as an opportunity to discover a unique regional heritage, and an attraction as part of culinary tourism, which has been an increasingly popular type of tourism. This article is a result of an analysis conducted by the daily “Dziennik Bydgoski,” with particular consideration of restaurants. Its purpose is to acquire knowledge on food consumption and culina ry traditions in the twenty-year interwar period, as well as many cultural events organized by restaurants. Information reported in advertisements reveals the role of food and customs related to it and consumer preferences; therefore, it as an important testimony to one of the cultural aspects of Bydgoszcz.